Analisis Cara Kerja Turbin Angin Sumbu Vertikal - Putri, Salsabillah Shiva; ., Sudarti; ., Yushardi (CV. ITTC INDONESIA, 2023)
Wind is the movement of air from an area with high pressure to an area with low pressure. Wind energy is one of the many abundant renewable energies. One example of the use of wind energy in Indonesia is the Wind Power Plant. A vertical axis wind turbine is a wind turbine that moves vertically where its axis is perpendicular to the ground surface. The advantage of this vertical axis windmill is that the turbine is not always directed towards the wind. The disadvantage of vertical axis wind turbines is that their efficiency is lower than horizontal axis wind turbines because there is lower wind speed and air resistance. In this article we will explain about vertical axis wind turbines, Wind Power Plants, and how wind turbines work. The research method used in writing this article is the literature study research method by reviewing several articles. From the research that has been carried out, the results obtained are an understanding of vertical axis wind turbines and wind power plants.